Science 2018 mysteries / Nur Azmina Mohamad Zamani - Mohamad Zamani, Nur Azmina (Corporate Communication Unit, Universiti Teknologi MARA, Perak Branch, 2019)
The objectives of the programme were to introduce UiTM Tapah Campus to school communities, and to provide opportunities for primary school students from rural areas to experience con-ducting science experiments independently in a proper lab. For UiTM Tapah students, this programme offered them chances to apply and share their knowledge of science concepts to the primary school students, with the hope that this could trigger positive changes and improvement to the young minds.